2005
DOI: 10.1038/oby.2005.139
|View full text |Cite
|
Sign up to set email alerts
|

Obstructive Sleep Apnea in Extremely Overweight Adolescents undergoing Bariatric Surgery

Abstract: Repeat polysomnograms were performed after significant weight loss. Comparisons were made between pre-and postoperative polysomnographic data. Results: Nineteen of 34 patients (55%) who underwent bariatric surgery were diagnosed with OSA. Subsequent to surgery, 10 of these patients returned for follow-up polysomnographic testing. After significant weight loss (mean, 58 kg), OSA severity markedly decreased in all patients (median apnea-hypopnea index at baseline vs. after weight loss, 9.1 vs. 0.65). Discussion:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
118
0
6

Year Published

2006
2006
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 243 publications
(129 citation statements)
references
References 31 publications
5
118
0
6
Order By: Relevance
“…Prevalence is higher among obese children 55,56 and may be Ն50% among adolescents with severe obesity. 57 Symptoms that parents may notice are loud snoring with pauses in breathing, restless sleep, and daytime somnolence. On physical examination, children may have tonsillar hypertrophy, although obstructive sleep apnea can occur in the absence of tonsillar hypertrophy or after removal of tonsils and adenoids.…”
Section: Sleep Problemsmentioning
confidence: 99%
“…Prevalence is higher among obese children 55,56 and may be Ն50% among adolescents with severe obesity. 57 Symptoms that parents may notice are loud snoring with pauses in breathing, restless sleep, and daytime somnolence. On physical examination, children may have tonsillar hypertrophy, although obstructive sleep apnea can occur in the absence of tonsillar hypertrophy or after removal of tonsils and adenoids.…”
Section: Sleep Problemsmentioning
confidence: 99%
“…In the pediatric population, the risk for developing SDB is fourfold greater in obese children than in children who are not obese (2). Although the prevalence of SDB in all children is believed to range from 2 to 3% (3)(4)(5), the prevalence in adolescents who are morbidly obese exceeds 50% (6,7). Obesity is therefore strongly associated with abnormal upper airway control during sleep across all age groups.…”
mentioning
confidence: 99%
“…Silvestri and coworkers reported that 59% of children referred to a sleep clinic and evaluated with polysomnography had OSAHS [13]. Kalra and coworkers described 55% of obese adolescents selected for bariatric surgery that underwent polysomnography had OSAHS [14]. Redline and coworkers made one of the few population-based studies which included 399 children between 2 -18 years old, and found obesity as the principal risk factor for OSAHS with an odds ratio (OR) of 4.5 (95% confidence interval 1.58 -13.3) [15].…”
Section: Discussionmentioning
confidence: 99%